Psychological assessment and intervention at the Boston Marathon - Brown, J. L.; Raeder, R.; Troyanos, C.; Dyer, K. S. (Sports Medicine, 2024)
The Boston Marathon is a highly regarded event in the running world, not just for its prestige and challenging course, but also for its implementation of a psychology team to support runners. The 2013 Boston Marathon bombings underscored the essential role that mental health support plays at this event, prompting the development and expansion of its innovative care model. This review critically outlines, evaluates, and analyzes the approach and effectiveness of the psychological care model provided to runners on race day as part of the Boston Marathon medical team, including the standard of care, how it functions, and best practices for other marathons. The implications for this review contribute to the increasing trend of providing psychological care in marathon and other athletic settings, and to provide a framework for standardizing assessment and intervention procedures for both elite and novice runners.